PEMBELAJARAN PEMECAHAN MASALAH PENGUKURAN PANJANG PADA SISWA SD KELAS 2 MENGGUNAKAN MODEL PEMBELAJARAN KONTEKSTUAL - Indah Susanti; Sylvia Rabbani (IKIP Siliwangi, 2020)
This research purpose to learning problem solving length measurement using contextual learning models. The research was implemented on second grade students in one of in elementary school in Cimahi. The method used is a qualitative descriptive. The instruments used are, problem solving questions, interview orientation, observation sheets, and validated questionnaire. The problem solving analysis was obtained from the result of students' response/answer. We need to use questionnaire for getting informations from students' opinion. The result of the research test show that the condition of students using contextual learning models has a higher average, compared to the condition of students when they have not gotten contextual learning in learning problem solving skills. Additionally, there's a positive response to mathematics and an influence on students' mathematical problem solving abilities. It is recommended for educators to using the contextual learning model as one of the choice models in Mathematics subjects.